Automatic processes in aggression: Conceptual and assessment issues. Issue 1 (January 2015) - Bluemke, Matthias; Teige‐Mocigemba, Sarah
<x xml:space="preserve">Abstract</x> This editorial to the special section "Automatic Processes in Aggression: Conceptual and Assessment Issues" introduces major research lines, all of which culminate in recent advances in the measurement of automatic components in aggressive behavior. Researchers of almost all psychological disciplines have stressed increasingly the importance of automatic components to gain a comprehensive psychological understanding of human behavior. This is reflected in current dual‐process theories according to which both controlled processes and rather automatic processes elicit behavior in a synergistic or antagonistic way. As a consequence, complementing self‐reports (assumed to assess predominantly controlled processes) by the use of implicit measures (assumed to assess predominantly automatic processes) has become common practice in various domains. We familiarize the reader with the three contributions that illuminate how such a distinction can further our understanding of human aggression. At the same time, it becomes evident that there is a long way that method‐oriented researchers need to go before we can fully comprehend how to best measure automatic processes in aggression. We see the present special section as an invigorating call to contribute to this endeavor. Aggr. Behav. 41:44–50 2015. © 2014 Wiley Periodicals, Inc.